OBSERVATIONS ON SOME SPECIES OF THE ORCHID GENUS RENANTHERA LOUREIRO - UWAY WARSTTA MAHYAR (Research Center for Biology, 1988)
A partial revision of Renanthera based on specimens preserved in Herbarium Bogoriense,Rijksherbarium Leiden and living collections maintained in Bogor Botanic Gardens is carried out.Nine species are treated including the newly proposed variety R.coccinea var, holltumii.Complete descriptions and illustrations as well as key to species and varieties treated are presented.R.sarcanthoides is excluded from Renanthera and transfered to Porphyrodesme